Hubungan Kualitas Tidur dengan Ansietas pada Penderita Asma Bronkiale - Dhiandra Dwi Hapsari; Harsini .; Hartono . (Nexus Kedokteran Klinik, 2012)
Background: Asthma is chronic inflammatory disease. Anxiety is psychiatric condition that is often found in many aspect of health one of which is asthma. Sleep disorders commonly found in patients with known asthma nocturnal. This study aimed to determine the relationship between sleep quality and anxiety of asthma patient. Methods: This study was observational by using cross-sectional design. The sample was selected by fixed exposure sampling from out patients who visited Pulmonology Clinics, RSUD Dr. Moewardi Surakarta. This research was held on April - May 2012. The data was collected by interview and some datas taken from the medical records. The data was analyzed using Chi-Square model, run on Statistical Product and Service Solution (SPSS) 18.00 for Windows. Results: Samples sizes were 30 asthma patients with anxiety and 30 asthma patient without anxiety. The results of this study showed that there is difference of sleep quality between asthma patient with anxiety and without anxiety. Asthma patient who were anxiety had 0.13 times higher risk for experiencing poor sleep quality than those who were without anxiety (OR = 0.13; p < 0.05). Conclusions: There is relationship between the sleep quality with anxiety of asthma patient. It is a strong association and statistically significant. The higher the level of anxiety, the higher the risk for poor quality sleep. Keywords: Asthma bronchiale, anxiety, sleep quality.